2014
DOI: 10.3109/19390211.2013.859212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Properties ofGongronema latifoliumin Phospholipon 90H Based Solid Lipid Microparticles (SLMs): An Antidiabetic Study

Abstract: Gongronema latifolium-loaded SLMs exhibited a good hypoglycemic effect and could be used for the treatment of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In this study, we demonstrated the inhibitory actions of four pregnane phytochemicals alongside their source chromatographic fractions derived from GLB against α-amylase, α-glucosidase and sucrase in vitro. The observed inhibitory potential of the pregnane-rich chromatographic fractions derived from GLB provides mechanistic insights into the in vivo anti-hyperglycaemic and anti-diabetic activities of various extracts from GLB extensively reported for over a decade [18][19][20]28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated the inhibitory actions of four pregnane phytochemicals alongside their source chromatographic fractions derived from GLB against α-amylase, α-glucosidase and sucrase in vitro. The observed inhibitory potential of the pregnane-rich chromatographic fractions derived from GLB provides mechanistic insights into the in vivo anti-hyperglycaemic and anti-diabetic activities of various extracts from GLB extensively reported for over a decade [18][19][20]28].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the leaves are incorporated into a tea blend that is mainly marketed to diabetes mellitus patients in the United States [16,17]. Several in vivo studies have helped to provide support for the ethnopharmacological use of GLB against hyperglycaemia, obesity, and diabetes [18][19][20]. For instance, methanol extracts alone and in combination with glibenclamide decreased the blood glucose from 1 to 6 h post-treatment in alloxan-induced hyperglycaemic rats [21].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO estimates that 70–80% of the people in developing countries use traditional medicine as a major source of health care [25]. GL is a herb that has long been an integral part of African traditional medicine and its beneficial properties have been well documented, especially as an antidiabetic herb [1, 9, 11, 26, 27]. In this study, we investigated an ethanolic extract of GL because similar extracts have been reported to be the most efficacious in exerting the anti-diabetic effect [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacological activities of GL extracts have been studied and reported, which provided experimental support for the empirical ethnopharmacological use of this plant in folk medicine. For example, anti-inflammatory [6], antifungal [7], anti-laxative [8] and antidiabetic [9, 10] activities have been reported. Over the past two decades, different parts of GL have been found to contain saponins, anthraquinones, alkaloids, β-sistosterol, sitostenone, lupenyl esters, pregnance ester, glucosides, and essential oils [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Aqueous and ethanolic leaf extracts of the plant have been reported to increase the frequency of spontaneously contracting tissues and directly stimulate uterine contractions in albino rats. 18 Similarly, ethanolic extracts of the leaves and stem of N. laevis have been reported to possess antioxidant activity in diabetic rats. 19 Since the fundamental importance of using plant-based medicines is their relative safety compared with synthetic drugs, and affordability of treatment, the objectives of this study were to formulate SLMs encapsulating N. laevis leaves extract and to study its analgesic/anti-nociceptive property.…”
Section: Introductionmentioning
confidence: 99%